Correlation and agreement of olfactory perception assessed by the Connecticut Chemosensory Clinical Research Center olfactory test and the Brief-Smell Identification Test - Marcello Bailarini Aniteli; Fernando Augusto Lima Marson; Fernanda Rodrigues Cunha; Eulália Sakano (Brazilian Journal of Otorhinolaryngology, 2022)
Introduction: Assessing olfactory perception in olfactory disorders is of utmost importance in therapy management. However, the University of Pennsylvania Smell Identification Test and the Sniffin’ Sticks are the only tests validated in Brazil. Objectives: To evaluate the correlation and agreement between the Chemosensory Clinical Research Center olfactory test and the Brief-Smell Identification Test – University of Pennsylvania Smell Identification Test – in healthy participants and in participants with olfactory disorders based on the results and technical aspects of both tests. Methods: Fifty participants without olfactory complaints and 50 participants with olfactory disorders who underwent the Chemosensory Clinical Research Center olfactory test and the Brief-Smell Identification Test were included. The following tests were used for statistical analysis: Mann-Whitney U test, Spearman’s correlation, intraclass correlation coefficient and Bland-Altman plot. An alpha error (significance level) of 0.05 was considered in the statistical analysis. Results: Both tests were effective in distinguishing the groups without the presence of overlapping values ​​for the measured markers. Additionally, there was a strong correlation between Spearman’s correlation and intraclass correlation coefficient between the tests and for both nostrils. However, the correlations were lower when the groups were individually evaluated. The Bland-Altman plot showed no bias when all participants were simultaneously evaluated. Conclusions: The tests to assess olfactory perception presented a high level of agreement. In our sample, we could infer that the Connecticut Chemosensory Clinical Research Center olfactory test is similar to the Brief-Smell Identification Test and can be used in the routine diagnosis of patients with complaints of olfactory disorders, considering the advantage of its low cost.